Professional Development Activities: Perception and Experiences of Secondary Level Teachers - Parajuli, Raju (Studies in ELT and Applied Linguistics, 2025)
Due to the changing nature of time, learners' varied needs and explosion of new knowledge and scientific invention, our usual teaching techniques might not function efficiently to enhance better learning environment. Effective teaching-learning can be maximized when teachers continuously involve themselves in professional development activities. However, the activities that teachers employ to be professionally equipped have not been explored in the context of study area. In this regard, this study aims to explore the activities related with the professional development adopted by secondary level teachers. The researcher adopted survey design (census data) under quantitative research method. It is based on the data from structured-questionnaire among 122 secondary level teachers from 31 secondary level schools of Tansen Municipality of Palpa district. The sample size is confined to those who are teaching Science, Math, Nepali and English subject in secondary level. Univariate analysis is used to explore the socio-demographic and professional development characteristics of the respondents. The results revealed that seven out of ten teachers are associated with professional development. And bivariate analysis is used to assess the effect of school type, and gender on professional development. Four out of five female teachers are associated with professional development. Results further showed that most of the teachers have enrolled in education faculty which helps teachers to be pedagogically competent. Most of the teachers are professionally aware to update themselves for teacher development. This study provides new insight on professional development in the sense that all the teachers have adopted fundamental strategies of professional development.